Exploring Australian pharmacists' views toward reducing the risk of medicines‐related harm in aged care residents - Sheraz Ali; Colin M. Curtain; Gregory M. Peterson; Mohammed S. Salahudeen (Wiley, 2023)
Abstract Medicines‐related harm is common in older people living in residential aged care facilities (RACFs). Pharmacists offering services in the aged care sector may play a key role in reducing medicines‐related injury. This study aimed to explore Australian pharmacists' views toward reducing the risk of medicines‐related harm in older residents. Qualitative, semi‐structured interviews were conducted with 15 Pharmacists across Australia providing services (e.g., through the provision of medication reviews, supplying medications, or being an embedded pharmacist) to RACFs identified via convenience sampling. Data were analyzed by thematic analysis using an inductive approach. Medicines‐related harm was thought to occur due to polypharmacy, inappropriate medicines, anticholinergic activity, sedative load, and lack of reconciliation of medicines. Pharmacists reported that strong relationships, education of all stakeholders, and funding for pharmacists were facilitators in reducing medicines‐related harm. Pharmacists stated that renal impairment, frailty, staff non‐engagement, staff burnout, family pressure, and underfunding were barriers to reducing medicines‐related harm. Additionally, the participants suggested pharmacist education, experience, and mentoring improve aged care interactions. Pharmacists believed that the irrational use of medicines increases harm in aged care residents, and medicines‐specific (e.g., sedative load) and patient‐specific risk factors (e.g., renal impairment) are associated with injuries in residents. To reduce medicines‐related harm, the participants highlighted the need for increased funding for pharmacists, improving all stakeholders' awareness about medicines‐associated harms through education, and ensuring collaboration between healthcare professionals caring for older residents.